2019
DOI: 10.1017/s1092852919001500
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin augmentation for resistant obsessive–compulsive disorder: a double-blind placebo-controlled clinical trial

Abstract: Background and objective.Glutamate dysfunction has been shown to be associated with pathophysiology of obsessive–compulsive disorder (OCD). Our objective is to survey the effects of pregabalin (a glutamate-modulating agent) as an augmenting treatment for resistant OCD.Patients and methods.In this 12-week double-blind placebo-controlled clinical trial, 56 patients with resistant OCD were randomly allocated to receive either pregabalin or placebo plus their current medication (sertraline). Yale–Brown Obsessive C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Three DB-RCTs were included, two assessing adjunctive pregabalin for the treatment of PTSD [ 47 ] and OCD [ 48 ] and one assessing gabapentin for the treatment of PD [ 49 ] (also see Supplementary Appendix, Table 2 ). Quantitative synthesis was not conducted due to clinical and methodological heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Three DB-RCTs were included, two assessing adjunctive pregabalin for the treatment of PTSD [ 47 ] and OCD [ 48 ] and one assessing gabapentin for the treatment of PD [ 49 ] (also see Supplementary Appendix, Table 2 ). Quantitative synthesis was not conducted due to clinical and methodological heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Several strategies have been used for the treatment of OCD patients who do not respond to SSRI medications. Augmenting the current regimen with another serotonergic enhancer is one strategy (Ravizza et al , 1996; Denys et al , 2004; Marazziti et al , 2008; Mowla et al , 2016). Adding antipsychotics or glutamatergic modulators to the SSRIs are other tactics used to approach these patients (Komossa et al , 2010; Matsunaga et al , 2011; Fineberg et al , 2015; Kishi et al , 2018; Talaei et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There is no standard cutoff point for YBOCS. A decline of at least 35% in YBOCS score was considered as response rate in this trial according to the results of similar prior studies (Sahraian et al , 2018; Mowla and Ghaedsharaf, 2020; Sahraian et al , 2021). The study psychiatrist assessed the adverse effects at each visit and recorded them.…”
Section: Methodsmentioning
confidence: 99%
“…Pregabalin, a gamma-aminobutyric acid analog, modulates calcium channels and has been approved for its use in epilepsy, neuropathic pain, fibromyalgia, and generalized anxiety disorder. Anecdotal reports showed some efficacy of pregabalin for OCD and a recent placebocontrolled randomized trial showed positive results respect to placebo in a dose range between 75 and 225 mg. 127 A randomized controlled trial at the McMaster University in Canada investigated the effects of pregabalin in a flexible dose up to 600 mg for 8 weeks as an addition to SRIs treatment in resistant OCD. According to clinicaltrils.gov (last update mid-September 2020), the trial has concluded, but results are still not provided and, to the best of our knowledge, there are not available publications yet.…”
Section: Naproxen and Immunoglobulins For Pans/pandasmentioning
confidence: 99%